High reliability teams: new directions for disaster management and conflict. Issue 4 (7th October 2014) - A. Jehn, Karen; Techakesari, Pirathat
Abstract : Purpose: – The aim of this paper is to present a framework that can be used to identify detrimental team processes in high reliability teams (HRTs), such as conflict, asymmetric perceptions and stress and coping appraisals, and develop interventions that eliminate these detrimental team processes. In addition, this paper suggests new directions for future disaster management and conflict research. Design/methodology/approach: – This framework is developed based on past theories (i.e. Intragroup Conflict Theory and Biopsychosocial Model of arousal regulation) and their associated empirical studies. Findings: – The present article brings a multi-method, multi-level approach to examine the prevalence of detrimental team processes in HRTs, their impact on performance and stress-related health outcomes and how they can be prevented or managed. Originality/value: – This paper provides a novel conceptual framework that highlights the importance of considering human factors and team processes in improving the response speed, accuracy and efficiency of high reliability team members and ensuring the health and well-being of both responders and recipients of care.